Handgrip strength and risk of cognitive impairment across different glucose metabolism statuses: insights from the CHARLS study - Wang, Shiqi; Li, Liangchen; Yu, Jia; Sun, Xianli; Chen, Jianqiao (Frontiers in Aging Neuroscience, 2025)
BackgroundBoth low handgrip strength (HGS) and abnormal glucose metabolism have been implicated in an increased risk of cognitive impairment. However, whether HGS interacts with glucose metabolism status to influence cognitive function remains unclear. This study explores the relationship between HGS and cognitive impairment risk among middle-aged and older Chinese adults and examines the potential modulation of this association by glucose metabolism status.MethodsData from the China Health and Retirement Longitudinal Study (CHARLS) collected in 2011 and 2018 were analyzed, including 7,301 participants aged ≥ 45 years. Cognitive impairment was the primary outcome. Logistic regression and restricted cubic spline (RCS) analyses were applied to evaluate the association between HGS and cognitive impairment risk across different glucose metabolism statuses.ResultsThe study included 7,301 participants (mean age: 58.8 ± 8.9 years; 49.3% female). Over a 7-year follow-up, the mean cognitive function score declined from 12.05 ± 3.30 to 7.75 ± 5.70. After adjusting for confounders, logistic regression analyses indicated that higher HGS was significantly associated with a lower risk of cognitive impairment. Participants in the highest HGS quartile (Q4) had a significantly reduced odds of cognitive impairment compared to those in the lowest quartile (Q1) (odds ratio [OR]: 0.59, 95% confidence interval [CI]: 0.49–0.71; P < 0.001). RCS analysis demonstrated a significant negative linear correlation between HGS and cognitive impairment across individuals with normal glucose regulation, prediabetes, and diabetes (P < 0.001). The interaction p-value was 0.277, indicating no significant differences in this association among glucose metabolism subgroups.ConclusionHigher HGS is significantly associated with a reduced risk of cognitive impairment among middle-aged and older individuals, irrespective of glucose metabolism status. These findings suggest that HGS assessment could be a valuable universal tool for evaluating cognitive impairment risk, regardless of metabolic conditions.